The Virtual Art Exhibition between Modernization and Diffusion in the Age of Digitization: The Exhibition of Art Education Students at the Hashemite University as a Model - Aldwairi, Issam; BaniMilhem, Osamah; Ayesh , Saleem (Dirasat: Human and Social Sciences, 2023)
Objectives: This research aims to shed light on the importance of using virtual art exhibitions. It also aims to identify the practical steps for designing a virtual digital art gallery. Methods: The research utilizes a qualitative methodology to collect and analyze data. Semi-structured interviews, with open-ended questions, were conducted to collect the essential data from the participants. To achieve identify the practical application steps for designing the virtual art gallery, virtual art halls were designed, step by step, to demonstrate the design process. Artworks of the Hashemite University students were used to elaborate on the idea of the virtual exhibition to be created as well as the way via which those artworks are showcased virtually. Results: The research showed that the spread of the COVID-19 pandemic helped shed a more focused light on the importance of virtual exhibitions. Results also showed the notion that virtual exhibitions have made it easier for people to attend exhibitions remotely if they can not make it in-person participation as in the traditional exhibition. The practical procedures that were explained when designing the virtual exhibition also facilitated the increase in public awareness and students' knowledge of how to create the virtual exhibitions. Conclusions: The research recommends the need to create a digital design academy to facilitate virtual design, integrate hybrid teaching materials with traditional methods, and promote 3D design software adoption, making virtual design a part of daily life for the university, local community, and the marketplace.